DETERMINATION OF THE PRESENCE OF CAMPYLOBACTER FETUS SUBSP. VENEREALIS IN ALPACAS AND LLAMAS IN THE PUNO REGION - Pasquel H., Silvia (2011)
The presence of Camplylobacter fetus subsp. venerealis in South Americancamelides was evaluated. The animals were from the INIA-Quimsachata Research Centrelocated in the department of Puno. Vaginal and preputial swabs were collected from 244alpacas and llamas between February and March 2007. Samples were analyzed by thedirect immunofluorescence test using a commercial conjugate. None of the samplesresulted positive. The probable mean prevalences using the @Risk software were 0.069 and 0.096% in alpacas and llamas respectively.